Magnetically‐actuated microcages for cells entrapment, fabricated by laser direct writing via two photon polymerization - Popescu, Roxana Cristina; Calin, Bogdan Stefanita; Tanasa, Eugenia; Vasile, Eugeniu; Mihailescu, Mona; Paun, Irina Alexandra (Frontiers in Bioengineering and Biotechnology, 2023)
The manipulation of biological materials at cellular level constitutes a sine qua non and provocative research area regarding the development of micro/nano-medicine. In this study, we report on 3D superparamagnetic microcage-like structures that, in conjunction with an externally applied static magnetic field, were highly efficient in entrapping cells. The microcage-like structures were fabricated using Laser Direct Writing via Two-Photon Polymerization (LDW via TPP) of IP-L780 biocompatible photopolymer/ iron oxide superparamagnetic nanoparticles (MNPs) composite. The unique properties of LDW via TPP technique enabled the reproduction of the complex architecture of the 3D structures, with a very high accuracy i.e. about 90 nm lateral resolution. 3D hyperspectral microscopy was employed to investigate the structural and compositional characteristics of the microcage-like structures. Scanning Electron Microscopy coupled with Energy Dispersive X-Ray Spectroscopy was used to prove the unique features regarding the morphology and the functionality of the 3D structures seeded with MG-63 osteoblast-like cells. Comparative studies were made on microcage-like structures made of IP-L780 photopolymer alone (i.e. without superparamagnetic properties). We found that the cell-seeded structures made by IP-L780/MNPs composite actuated by static magnetic fields of 1.3 T were 13.66±5.11 folds (p<0.01) more efficient in terms of cells entrapment than the structures made by IP-L780 photopolymer alone (i.e. that could not be actuated magnetically). The unique 3D architecture of the microcage-like superparamagnetic structures and Formatted: French (France) PAGE \* Arabic \* MERGEFORMAT 2 their actuation by external static magnetic fields acted in synergy for entrapping osteoblast-like cells, showing a significant potential for bone tissue engineering applications.